Piety and Modernity : The Dynamics of Religious Reform in Northern Europe, 1780-1920 - Jarlert, Anders (Book collections on Project MUSE., 2012)
This book examines the dynamics of religious reform from the point of view of piety and devotional life between 1780 and 1920 in Britain, Ireland, Scandinavia, Germany, and the Low Countries. The 'long' nineteenth century saw the introduction of devotional organizations as a means of channeling popular religion. This era also witnessed the translation and publication of devotional books, journals, and pamphlets on a massive scale. This edited volume explores the nature of pious reforms in such areas as liturgy, saint cults, pilgrimage, confraternities, hymns, and Bible translation, with an emphasis on the changing patterns in religious expression at the collective and individual level, the growing influence of home missions, and the relations between piety and print culture--